O tej muzyce. Poezja Wespazjana Kochowskiego jako tworzywo „sarmackich” piosenek Jacka Kowalskiego - Marcin Janiszkiewicz (Meluzyna: dawna literatura i kultura)
The aim of the article is to present the intertextual connections between the insufficiently researched songs of Jacek Kowalski (the material includes songs published in the years 1986–2020) and the poetry of Wespazjan Kochowski. The analysis focused on the dialogical and palimpsest dimensions of the works of a contemporary author, as well as on the architextual relations present there.